2019
DOI: 10.4103/ijpvm.ijpvm_422_17
|View full text |Cite
|
Sign up to set email alerts
|

Health services management in Turkey: Failure or success?

Abstract: Background:The unfair distribution and delivery of health-care resources have been recognized as a problem in the worldwide. In the past 18 years, Turkey has undergone rapid social, cultural, and economic changes. The lifestyle and dietary habits of its people have also been changing, and the rates of diabetes, obesity, cancer, and other chronic diseases have increased dramatically over the past two decades. The health transformation program (HTP) has improved the Turkish health-care system since 2003. The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 20 publications
0
19
1
Order By: Relevance
“…This was supported by Srivastava K 2009, who confirms the strong association between urbanization and mental disorders. On the other side, this was inconsistent with a study from Turkey done by Demirbag et al 2017 on the evaluation of the life quality of workers in a cement factory, and found that there was no effect of residence on life quality of the studied workers, this could be explained by the efforts done by ministry of health in Turkey to reach the equity in health services in all areas (urban and rural) thus affecting behavior disorders (Bener et al 2019).…”
Section: Discussioncontrasting
confidence: 67%
“…This was supported by Srivastava K 2009, who confirms the strong association between urbanization and mental disorders. On the other side, this was inconsistent with a study from Turkey done by Demirbag et al 2017 on the evaluation of the life quality of workers in a cement factory, and found that there was no effect of residence on life quality of the studied workers, this could be explained by the efforts done by ministry of health in Turkey to reach the equity in health services in all areas (urban and rural) thus affecting behavior disorders (Bener et al 2019).…”
Section: Discussioncontrasting
confidence: 67%
“…Additionally, despite developments in recent years, health referral system cannot function properly in Turkey. 39 Such reasons make it easier for patients to reach the hospital and choose to die in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in that country suggested the need for specific methods to control costs, improve cost-efficiency, and monitor the impact of spending on health (33). Also, the need for physicians in urban health centers and the importance of pre-service and in-service training have been shown in similar studies (34,35). Contrary to our results, an investigation conducted in Canada rated physicians' clinical performance as good to excellent without the need for retraining and acquiring skills (36).…”
Section: Discussionmentioning
confidence: 94%